Influence of the cold cathode material on the operating mode of the pulse high-current vacuum diode in a microsecond range - Kolyada, Yu.E. (Вопросы атомной науки и техники, 1999)
The present work is aimed at the description of experimental results on the drop fraction of high-power electrical vacuum discharge and analysis of processes, which take place in cold cathodes working in microsecond range of pulses, and also on the influence of the material of a cold cathode on the operating mode of the pulse high-current vacuum diode.